Plastische Verformungsmechanismen in hochgradig kaltgewalzten, ultrafeinkörnigen Wolframblechen - Bonk, Simon Werner (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2019)
Cold rolled tungsten sheets are regarded as promising materials for high-temperature applications. The correlation of microstructural features with strain rate sensitive, mechanical properties of differently thick cold rolled tungsten sheets allows conclusions to be drawn on the plastic deformation mechanisms. Thus, the simultaneous increase in strength and ductility of the technically pure tungsten sheets at room temperature as well as their high-temperature behavior can be explained.